2020
DOI: 10.1152/ajplung.00001.2020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic activation of glucose-6-phosphate dehydrogenase controls the expression of genes involved in the pathogenesis of pulmonary hypertension through the regulation of DNA methylation

Abstract: Metabolic reprogramming is considered important in the pathogenesis of the occlusive vasculopathy observed in pulmonary hypertension (PH). However, the mechanisms that link reprogrammed metabolism to aberrant expression of genes, which modulate functional phenotypes of cells in PH, remain enigmatic. Herein, we demonstrate that, in mice, hypoxia-induced PH was prevented by glucose-6-phosphate dehydrogenase deficiency (G6PDDef), and further show that established severe PH in Cyp2c44−/− mice was attenuated by kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 49 publications
2
64
0
Order By: Relevance
“…We and others have recently proposed that DNA methylation and other epigenetic modifications potentially promote maladaptive gene expression, a determinant of inflammatory and hyperproliferative cell phenotype, in remodeled PA (Hu et al, 2019;Joshi et al, 2020;Potus et al, 2020). Furthermore, we recently showed that expression of Tet2, a DNA demethylase considered as a master regulator of differentiated fate of SMC This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We and others have recently proposed that DNA methylation and other epigenetic modifications potentially promote maladaptive gene expression, a determinant of inflammatory and hyperproliferative cell phenotype, in remodeled PA (Hu et al, 2019;Joshi et al, 2020;Potus et al, 2020). Furthermore, we recently showed that expression of Tet2, a DNA demethylase considered as a master regulator of differentiated fate of SMC This article has not been copyedited and formatted.…”
Section: Discussionmentioning
confidence: 99%
“…Male and female C57BL/6J mice (18-32 g) were purchased from the Jackson Laboratory and randomly divided into four groups: normoxia (Nx), normoxia+Sugen5416 (Nx+SU), hypoxia (Hx), and hypoxia+Sugen5416 (Hx+SU) groups. Mice in Nx group were placed in normoxic (21% O 2 ) environment and in Hx group were placed in a normobaric hypoxic chamber (10% O 2 ) for 6 weeks (Joshi et al, 2020). Mice in Nx+SU and in Hx+SU group received subcutaneous injection of SU5416 (20 mg/kg) once weekly during 3 weeks of Nx (21% O 2 ) or Hx (10% O 2 ) as previously described (Vitali et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these can reflect local DNA methylation signature in the setting of PAH. The other study by Joshi et al ( 17 ) unveiled the mechanisms that link reprogrammed metabolism to aberrant expression of functional phenotype-associated genes in PH. They suggest that functional TET2 is required for G6PD inhibition to reverse PH in mice.…”
Section: Discussionmentioning
confidence: 99%